2011
DOI: 10.1093/occmed/kqr180
|View full text |Cite
|
Sign up to set email alerts
|

Work-related stress among health professionals in northern Jordan

Abstract: Compared to physician specialists, general practitioners, dentists and pharmacists were significantly more stressed. Reported stress was associated with job title, being a woman and long working hours. Also uncooperative patients and heavy workloads were significant problems. Being irritable and having headaches and common colds were the most frequent health issues.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
59
5
11

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(92 citation statements)
references
References 10 publications
8
59
5
11
Order By: Relevance
“…Te opasnosti mogu uzrokovati alergije, toksične reakcije, preosjetljivost, kemijske ozljede itd. Psihološke opasnosti uključuju stres, kronični umor i sindrom izgaranja na poslu (4,13). One mogu biti izvor mnogobrojnih psihološ-kih tegoba, poput depresije i anksioznosti, ali i izvor nekih somatskih poremećaja, poput krvožilnih bolesti, povišenoga krvnog tlaka, neuroloških poteškoća i dr.…”
Section: Participants and Methodsunclassified
See 1 more Smart Citation
“…Te opasnosti mogu uzrokovati alergije, toksične reakcije, preosjetljivost, kemijske ozljede itd. Psihološke opasnosti uključuju stres, kronični umor i sindrom izgaranja na poslu (4,13). One mogu biti izvor mnogobrojnih psihološ-kih tegoba, poput depresije i anksioznosti, ali i izvor nekih somatskih poremećaja, poput krvožilnih bolesti, povišenoga krvnog tlaka, neuroloških poteškoća i dr.…”
Section: Participants and Methodsunclassified
“…Chemical hazards can cause allergies, toxic reactions, hypersensitivity, chemical injuries etc. Psychological hazards include stress, chronic tiredness and burn-out syndrome (4,13). Exposure to psychosocial hazards in the workplace not only produces psychological damage to individual employees such as depression and anxiety, but also causes somatic disorders such as cardiovascular diseases, hypertension, neurological disorders etc.…”
Section: Uvodmentioning
confidence: 99%
“…1 Studies conducted in other countries have demonstrated that there is a direct relationship between higher levels of stressors at work and presence of fatigue, sleep disturbances, depressive symptoms and drug consumption. [2][3][4][5] In Brazil, changes to how the job of teaching is organized, the advent of new requirements and competencies that are changing teaching activity, but without the means to provide compatibility, has created work overload. The factors mentioned above may be a source of complaints, mental disorders and absence from work.…”
Section: Introductionmentioning
confidence: 99%
“…• prolonged working time (6, 7); • uncooperative and/or "difficult" patients (10,11); • night work (12,13); • perception of a risk to themselves in the workplace (14); • limited free time to spend on after work activities (8,15,16); • limited support from colleagues (17);…”
Section: Introductionmentioning
confidence: 99%